EFEKTIVITAS PEMUNGUTAN DAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DI KOTA MAKASSAR - Ratna Sari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2021)
This study aims to determine the effectiveness of motor vehicle tax collection and revenue in SAMSAT Makassar City. The data in this study used primary data collected by conducting direct interviews with employees or related agencies. The steps for data analysis after collection are: 1) Data Reduction. Reducing data means summarizing, choosing the main things, focusing on the important things, looking for themes and patterns. 2) Data Presentation (Data Display). After the data is reduced, the next step is to display the data. In qualitative research, the presentation of bias data is carried out in the form of brief descriptions, charts, relationships, between categories, flowcharts and the like. 3) Data Verification (Couclusions drowing/verifiying). The final step in the data analysis technique is data verification. Data verification is carried out if the initial conclusions presented are still provisional, and there will be changes if not accompanied by strong supporting evidence to support at the next stage of data collection. Based on the results of the research that has been conducted, it can be seen that the effectiveness of motor vehicle tax collection and revenue at the Samsat Office Region I Makassar City has been effective because it is in accordance with the standard operating procedures of the Makassar City government. However, it is necessary to improve services by considering the conditions of the people in Makassar to be more effective and efficient in collecting motor vehicle taxes.